Case Report: Isolated Epileptic Seizures Associated With Anti-LGI1 Antibodies in a 7-Year-Old Girl With Literature Review - Wang, Ying; Zhang, Wei-Hua; Wang, Yuan (Frontiers in Pediatrics, 2022)
We described a 7-year-old girl with anti-LGI1 antibodies (LGI1-Abs) positivity presenting as the isolated epileptic seizures. Her refractory focal seizures did not respond to anti-seizures drugs, but responded rapidly to the immunotherapy. She was seizure-free at two years of follow-up. Reviewing the literatures, no isolated epileptic seizures reported as the phenotype of LGI1-Abs autoimmunity in children. Our study indicated that screening for LGI1-Abs was necessary for children with new-onset epileptic seizures